THE USE OF AUDIO VISUAL AS MEDIA IN ENHANCING STUDENTS’ LISTENING SKILL - Rosdiana (Getsempena English Education Journal, 2018)
Listening is a basic ability required in mastering English. The purpose of this article is to describe the utilization of audio visual media in improving listening skills of students majoring in STKIP Language BBG Banda Aceh. The main purpose of this research is 1) to know the application of learning development of audio-visual media in improving listening ability of first year English students of STKIP BBBG. 2) to know the increasing of listening ability of English student of second year students of STKIP BBBG after getting learning using audio visual media. This research is quantitative study. To achieve these objectives, purposive sampling is used which is focused on the first year student students semester II are taken as the subject of this research. Regarding the data analysis, mean, percentageandt-test scores for the dependent sample were employed. There sultindi cated that 1)thestudents’ English listening comprehension ability increased significantly after learning with video sand 2) students had positive attitude stoward susing video sin teaching listening skills.